1988
DOI: 10.1111/j.1432-1033.1988.tb13938.x
|View full text |Cite
|
Sign up to set email alerts
|

Attachment of human placental‐type alkaline phosphatase via phosphatidylinositol to syncytiotrophoblast and tumour cell plasma membranes

Abstract: Phosphatidylinositol anchors human placental-type alkaline phosphatase (PLAP) to both syncytiotrophoblast and tumour cell plasma membranes. PLAP activity was released from isolated human placental syncytiotrophoblast plasma membranes and the surface of tumour cells with a phospholipase C from Bacillus cereus. This was a specific event, not the result of proteolysis or membrane perturbation, but the action of a phosphatidylinositol-specific phospholipase C in the preparation. Soluble PLAP, released with B. cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Treatment with PIPLC released H3 15-precipitable material into the supernatant, whilst bromelain released both H3 15-and W6/32-precipitable material. These results are consistent with previous reports, where the action of B.cereus phospholipase C in releasing PLAP from the choriocarcinoma membranes has been shown to be due to a PIPLC contaminant in the preparation (Webb and Todd, 1988). Although molecules of 72 kDa were identified in 5T4 immunoprecipitates from treated cell lysates, no labelled molecules were precipitated with MAb 5T4 from supernatants generated from bromelain or PIPLC-treated cells.…”
Section: Enzymatic Digestionsupporting
confidence: 95%
“…Treatment with PIPLC released H3 15-precipitable material into the supernatant, whilst bromelain released both H3 15-and W6/32-precipitable material. These results are consistent with previous reports, where the action of B.cereus phospholipase C in releasing PLAP from the choriocarcinoma membranes has been shown to be due to a PIPLC contaminant in the preparation (Webb and Todd, 1988). Although molecules of 72 kDa were identified in 5T4 immunoprecipitates from treated cell lysates, no labelled molecules were precipitated with MAb 5T4 from supernatants generated from bromelain or PIPLC-treated cells.…”
Section: Enzymatic Digestionsupporting
confidence: 95%
“…The expression of hCG was shown to be required for spontaneous or EGF-stimulated differentiation (measured by hCG expression) of CTs (32). PLAP expression occurs on the brush border of differentiated trophoblasts (35), although whether this is linked to hCG production or some other aspect of the differentiation pathway is unknown. The appearance of ‫%03ف‬ of the nuclei in multinucleated units after 5 days (without the addition of EGF) was unaffected by S1P.…”
Section: Discussionmentioning
confidence: 99%
“…Other proteins that are often used as markers for syncytiotrophoblast are human placental lactogen (hPL; CSH1) (Gaspard et al 1980, Pidoux et al 2007) and human placental alkaline phosphatase (ALPP; Webb & Todd 1988, Guilbert et al 2002. Regarding CGB, former studies have already shown that BeWo cell fusion is not necessarily linked to CGB mRNA expression (Lin et al 1999).…”
Section: Introductionmentioning
confidence: 99%